The Metabolic Syndrome, Oxidative Stress, Environment, and Cardiovascular Disease: The Great Exploration. (9th July 2012) - Hutcheson, Rebecca; Rocic, Petra
Abstract : The metabolic syndrome affects 30% of the US population with increasing prevalence. In this paper, we explore the relationship between the metabolic syndrome and the incidence and severity of cardiovascular disease in general and coronary artery disease (CAD) in particular. Furthermore, we look at the impact of metabolic syndrome on outcomes of coronary revascularization therapies including CABG, PTCA, and coronary collateral development. We also examine the association between the metabolic syndrome and its individual component pathologies and oxidative stress. Related, we explore the interaction between the main external sources of oxidative stress, cigarette smoke and air pollution, and metabolic syndrome and the effect of this interaction on CAD. We discuss the apparent lack of positive effect of antioxidants on cardiovascular outcomes in large clinical trials with emphasis on some of the limitations of these trials. Finally, we present evidence for successful use of antioxidant properties of pharmacological agents, including metformin, statins, angiotensin II type I receptor blockers (ARBs), and angiotensin II converting enzyme (ACE) inhibitors, for prevention and treatment of the cardiovascular complications of the metabolic syndrome.